THE INFLUENCE OF THINK TALK WRITE TO IMPROVE THE TENTH GRADE STUDENTS’ WRITING SKILL AT SMA NEGERI 2 SEKAMPUNG (English Community Journal, 2022)
The objective of this research was to find out whether Think Talk Write on writing skill significant which was effective or not. This research used true experimental method. The population was all the tenth grade students which consisted of 189 students. The samples were taken by random sampling technique as many as 44 students. The data were collected by using test (pre and posttest). The result of the test was analyzed by independent sample t-test. The mean or average in posttest of experimental group was 78.868. It was higher than the mean or average posttest of the control group which was 60.532. The result of tobtained was 9.375 with the significant level p<0.05; df was 42 and ttable was 2.0181. Since the value of tobtained was higher than ttable, means null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It can be stated that teaching recount text using Think Talk Write was more significant effective on writing achievement than conventional method to the tenth grade students of SMA Negeri 2 Sekampung.